Cardio-Protective Effect Of Standardized Extract Of Clinacanthus Nutans Lindau Against Doxorubicin-Induced Toxicity - Esmailli, Kameh (2017)
The primary purpose of this thesis was to investigate cardio-protective effect of standardized leaf extract of Clinacanthus nutans (CN) against chemotherapy-induced cardio-toxicity. In the Far East, CN has been used traditionally to treat a wide range of diseases including herpes, cancer, fractures, diabetes, diuretic, jaundice, snake bites and kidney dysfunction. There are a number of CN products in market, however there is still lack of scientific evidence in terms of standardisation. Quality and safety of the plant raw material were examined using gravimetric analysis and microbial limit test (MLT).